Diesel engine air path control based on neural approximation of nonlinear MPC. (October 2019) - Moriyasu, Ryuta; Nojiri, Sayaka; Matsunaga, Akio; Nakamura, Toshihiro; Jimbo, Tomohiko
Abstract: This paper deals with a control design problem for a diesel engine air path system that has strong nonlinearity and requires multi-input and multi-output control to satisfy requirements and constraints. We focus on a neural network based approximation of nonlinear model predictive control (NMPC) for high-speed computation. Most neural approximation methods are verified only through simulation; further, the influence of approximation on the closed-loop performance has been not sufficiently discussed. In this study, we discuss this influence, and propose a new method to improve stability against degradation due to an approximation error. The control system is assembled using a neural network based controller, obtained by the proposed method, and an unscented Kalman filter. This system is verified both numerically and experimentally; the results demonstrate the capability of the proposed method to track the boost pressure, EGR rate, and pumping loss according to the reference values, and satisfy the constraints of compressor surge and choke. The high computation speed that can be achieved using a standard on-board ECU is also demonstrated using the approximated controller. Highlights: The proposed method realizes fast computation of nonlinear MPC. It approximates optimal control inputs with high accuracy using a neural network. It provides a new method to cope with stability degradation due to approximation. Its effectiveness is validated through an experiment using a real diesel engine. It can be applied to any other continuous variable system.